ANALYSIS OF ISLAMIC FINANCE DEVELOPMENT IN KAZAKHSTAN: OVERVIEW AND PROSPECTS - R. К. Sagiyeva; L. A. Kuanova (Экономика: стратегия и практика, 2019)
This article provides a discussion on the issues of Islamic finance development in Kazakhstan - an area which has not been critically addressed in the literature. As Islamic Finance has not been developed correctly for last 10 years in the country, the authors set a goal to study the past overview of the Islamic finance for identification obstacles that should be overcome for further development. Based on the analysis of the previous experience of application of Islamic financial law and instruments developed and proposed recommendations for implementation to the Islamic finance industry of Kazakhstan. There has been used the methods of applied research, scientific abstraction, system approach. The inference of the study result based on analysis the strengths and opportunities, weaknesses and threats of Islamic finance in order to minimize weaknesses and threats for the country economy and financial system. The results of the study can be used for the successful spread of Islamic Finance in Kazakhstan and for overcoming challenges. Furthermore, the results and the recommendations of the study can be applied by legislative and Executive authority for coordination strategic development program of Islamic Finance in Kazakhstan. Furthermore, developed recommendations during the study can be implemented in upgrade of Islamic finance low or could take a place in creation separate special low in field of Islamic finance in the country. The conclusion of the research illustrated that the problem of insufficient growth of Islamic finance is a more conservative system of Islamic finance, which was chosen in the country and there are number of restrictive barriers, prudential as well as social nature.